2020
DOI: 10.12928/telkomnika.v18i1.13293
|View full text |Cite
|
Sign up to set email alerts
|

Iris images encryption based on QR code and chaotic map

Abstract: In this paper an Iris image is encrypted based on QR (quick response) code and chaotic map. The main idea of the proposed system is generating a QR code depending on the input text and then extract the features from QR code by using convolution, these features are used for key generation. After that the permuted iris image is encrypted by using generated key, after that the resulting image will be encrypts using 2D logistic map. The randomness of generated key is tested using the measures of NIST, and quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…This study has applied three metrics; maximum deviation, entropy of the ciphered image, and color histogram. Mustafa et al [11] presented generating a quick response (QR) code relying on the input message and extracting the features used to generate the key. The features are extracted from QR codes using convolution.…”
Section: Introductionmentioning
confidence: 99%
“…This study has applied three metrics; maximum deviation, entropy of the ciphered image, and color histogram. Mustafa et al [11] presented generating a quick response (QR) code relying on the input message and extracting the features used to generate the key. The features are extracted from QR codes using convolution.…”
Section: Introductionmentioning
confidence: 99%
“…Ahmed et al [14] proposed a real-time significant model for the detection of the blood vein using mobile application under android with CLAHE technique as one layer of enhancement image. Shamsudeen et al [15][16][17][18] used HE with other techniques to enhance images in order to get more contrast image, but no studies using HE with many layers. All previous studies either complex or dealt with specific type of image size or type, but the suggested method which is used multilayers of standard algorithms of HE and CLAHE.…”
Section: Introductionmentioning
confidence: 99%
“…− Every perpendicular rectangle mk x M is split into ni boxes with dimensionsx mk including M points exactly. − Finally, these boxes are reshaped column by column to form a row of elements as illustrated in Figure5(b)[21,22].…”
mentioning
confidence: 99%